Histopathological Findings and Treatment of Intermuscular Lipoma in a Dog: A Rare Case - Ünsaldı, Emine; Polat, Eren; İncili, Canan Akdeniz; Eroksuz, Yesari; Can, Ümit Koray (My University, 2023)
In this study, the histopathological diagnosis and treatment of an intermuscular lipoma were reported in a dog. In the clinical inspection, there was a large mass in the caudal of the left femur and that the animal had difficulty in moving. On palpation, the mass was solid and painful. A decision was made to totally extirpate the mass, which was suspected to be a tumor. A wide skin incision was made from the caudal part of the left femur; the mass was separated from the surrounding tissues by blunt dissection and extirpated. Histopathological examination revealed that the mass was an intermuscular lipoma. In the postoperative period, the patient recovered completely and returned to its normal life.
Keywords: Dog; histopathology; mass; intermuscular lipoma